1984
DOI: 10.1139/g84-005
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic pairing in wheat–rye addition and substitution lines

Abstract: Chromosome pairing was examined in wheat–rye addition and substitution lines using the C-banding technique. It was found that both rye and wheat chromosomes affect each other's homologous pairing. The strongest diminution of wheat pairing (measured as bound arms per cell) was produced by chromosome 5R of rye (7.5 and 7.2% in 'Chinese Spring' – 'Imperial' and 'Holdfast' – 'King II' addition lines, respectively). The weakest diminution of wheat pairing was produced by chromosome 3R in the 'Chinese Spring' – 'Imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 11 publications
3
11
0
Order By: Relevance
“…Our results do not discriminate between the effects of individual rye chromosome. There is some evidence in this respect in earlier publications (Orellana et al, 1984;Gupta & Fedak, 1986). We confirm the observation of a general negative effect of rye telomeric heterochromatin on wheat pairing.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Our results do not discriminate between the effects of individual rye chromosome. There is some evidence in this respect in earlier publications (Orellana et al, 1984;Gupta & Fedak, 1986). We confirm the observation of a general negative effect of rye telomeric heterochromatin on wheat pairing.…”
Section: Resultssupporting
confidence: 89%
“…Moreover, it has been suggested that reduction of telomeric heterochromatin stabilizes rye chromosome behaviour at first metaphase in Triticale (Thomas & Kaltsikes, 1976;Merker, 1976;Schlegel, 1982). Orellana et al (1984), examined chromosome association in wheat-rye addition and substitution lines using C-banding. They found that both rye and wheat chromosomes affect each other's homologous pairing and discussed the role of constitutive heterochromatin in the failure of chromosome association at first meiotic metaphase.…”
Section: Introductionmentioning
confidence: 99%
“…In hexaploid triticale (Thomas and Kaltsikes, 1974;Lelley, 1975b;Schiegel, 1978a;Jung and Lelley, 1985a, b;Jung et aL, 1985;Galindo and Jouve, 1989) and in wheat-rye addition lines (Schlegel, 1978b;Orellana et a!., 1984), rye Fominaya and Orellana (1988) demonstrated a phenomenon of interference between wheat and rye chromosomes as a cause of the decrease of rye-rye and wheat-wheat homologous pairing observed at metaphase I in triticale with respect to their corresponding rye and wheat parents.…”
Section: Chromosome Constitution and Modificationsmentioning
confidence: 98%
“…In the F 1 s of these crosses, occasionally 2 univalents/laggards (Fig. 1B) were also observed which could be due to the precocious terminalization of 6R chiasmata (Orellana et al 1984). However, in the hybrid of RL 107-2, 4 univalents and laggards were observed (Fig.…”
Section: Resultsmentioning
confidence: 86%